PARAMETER OPTIMIZATION OF HYBRID MICROPERFORATED PANEL (MPP) AS A BROADBAND SOUND ABSORBER - Khairin Nisa, Ainil
The fundamental characteristic of Micro-perforated panel (MPP) based sound absorbers come with a narrow absorption bandwidth around one up to two octaves, thus limiting their applications in practice. This condition has motivated the use of series and parallel configurations to produce multi-resonance to obtain a wider overall absorption frequency range. Considering merit of each configuration, a hybrid MPP as combination of series and parallel in the MPP system was proposed to have a more rational thickness while wider absorption bandwidth can be preserved. However, the configuration and structure of the hybrid MPP are more complicated that arise a challenge to find the design parameters for the best absorption performance. In this study, an optimization technique formulation was developed by considering a minimum absorption of 0.8 with an absorption range of more than 3 octaves (> 2000 Hz). Three heuristic optimization methods widely applied in absorber systems, namely Genetic Algorithm (GA), Simulated Annealing (SA), and Cuckoo Search Algorithm (CSA) are considered. The result shows that the parameters obtained by the CSA lead to the highest average absorption coefficient of ???????? which is about 0.95 (>0.80) and the absorption range ?????????,???????? reaches more than 3000 Hz and ?????????,???????? increases by 22.7% from the initial parameter. Extending the optimization frequency range is useful to increase ?????????,???????? by 10-13% with an average ???????? of 0.95. Meanwhile, the use of cost function with RMSE approach can widen the absorption range of ?????????,???????? by 12.7% with an average ????????of 0.84. Moreover, reducing the panel thickness parameter value range can increase ?????????,???????? by 4.0% with an average ????????of 0.86 and the absorption range of ?????????,???????? increases by 15.0%, with an average ???????? of 0.95 from the initial parameter. Considering the results, the optimization techniques used in this study are able to produce better parameters for targeted absorption characteristics.